2020
DOI: 10.1186/s12891-020-03401-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical function and lean body mass as predictors of bone loss after hip fracture: a prospective follow-up study

Abstract: Background: Predictors of bone deterioration after hip fracture have not been well characterized. The aim of this study was to examine the associations of physical function and lean body mass (LBM) with loss of bone density and strength in older people recovering from a hip fracture. Methods: A total of 81 over 60-year-old, community-dwelling men and women operated for a hip fracture participated in this 1-year prospective follow-up study. Distal tibia total volumetric bone mineral density (vBMD TOT , mg/cm 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…While it has been investigated in various surgical specialties, the utility of φ as an indicator of post-operative complications within the fields of orthopaedic surgery and musculoskeletal health has not been well described. Existing studies have primarily focused on geriatric native hip fractures: φ has been shown to predict the occurrence of hip fractures and post-fixation outcomes [30][31][32]. In arthroplasty, φ has not been previously investigated despite sharing desired outcomes and complications with the trauma population.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been investigated in various surgical specialties, the utility of φ as an indicator of post-operative complications within the fields of orthopaedic surgery and musculoskeletal health has not been well described. Existing studies have primarily focused on geriatric native hip fractures: φ has been shown to predict the occurrence of hip fractures and post-fixation outcomes [30][31][32]. In arthroplasty, φ has not been previously investigated despite sharing desired outcomes and complications with the trauma population.…”
Section: Introductionmentioning
confidence: 99%